Pengelolaan Antrian Kapal Pompong Berbasis Teknologi di Pelabuhan Sekupang-Belakang Padang - Friadi, John; Masril, M. Abrar; Jufri, Muhammad; Caniago, Deosa Putra; Hernando, Luki; Munir, Zainul; Aritonang, Mhd Adi Setiawan; Aswirawan, M.Y Meinadia Sekarkinanti (Penerbit Goodwood, 2025)
Purpose: The interactive whiteboard serves as an information hub in the queue system, displaying queue numbers in real-time and enabling user interaction. Its key features include automatic queue number management, access to additional information, and integration with technologies such as printers and QR codes. Its benefits include time efficiency, an improved customer experience, and flexibility for use across various sectors, making it an innovative solution to enhance service effectiveness. Methodology: The PKM program began with an initial analysis through site visits to the port and interviews with PPMS members. Activities included theory, practice, and queue technology simulations. Preparations involved coordination, provision of equipment, and materials. PPMS actively participated by providing facilities and attending training. Lecture, demonstration, and practice methods were applied to enhance understanding. Results: The ship queueing system at the port enhances loading and unloading efficiency. Interactive whiteboards simplify queue management with real-time features, QR codes, and technology integration. Surveys show that 90% of users find this system easy to use. Conclusions: This service proves that the application of technology in managing the queue of pompong ships at ferry ports has a significant positive impact. Limitations: The passage lacks specific data, overlooks challenges like maintenance and system failures, and has contextual gaps. It ignores scalability, usability for older users, and environmental constraints, limiting its assessment of the system’s effectiveness. Contribution: This community service demonstrates that the implementation of technology in managing the queue of pompong boats at the ferry port has proven effective in reducing waiting times, streamlining departure flows, and enhancing passenger and boat operator satisfaction.